Distribución de Raninoides benedicti Rathbun, 1935 (Brachyura: Raninidae), con notas ecológicas y observación de una alometría de crecimiento de las quelas - Hendrickx, M E (Universidad de Costa Rica, 1990)
New records oC Raninoides benedicti are reported and the normem distriblllion limit of this species is extended 10 Rocas Consag, including fint collections along the east coast oC the Gulf of California. A large series of specimens including males and females of 3.5:0 23.6 mm of carapace width, was obtained and an allomeuy cf growth of the male cheliped was detected.